Therapeutic monoclonal antibody for sporotrichosis - Almeida, Sandro (Frontiers in Microbiology, 2012)
Sporotrichosis is a chronic subcutaneous mycosis that affects either humans or animals and occurs worldwide. This subcutaneous mycosis had been attributed to a single etiological agent, Sporothrix schenckii. S. schenckii exhibits a considerable genetic variability, where recently, was suggesting that this taxon consists of a complex of species. Sporotrichosis is caused by traumatic inoculation of the fungus, which is a ubiquitous environmental saprophyte that can be isolated from soil and plant debris. The infection is limited to the cutaneous forms but, recently, occurrences of more severe clinical forms of this mycosis were described, especially among immunocompromized individuals. The immunological mechanisms involved in prevention and control of sporotrichosis are still not very well understood. Some works suggest that cell-mediated immunity plays an important role in protecting the host against S. schenckii. In contrast, the role of the humoral immune response in protection against this fungus have not been studied in detail. In a previous study, we showed that antigens secreted by S. schenckii induce a specific humoral response in infected animals, mainly against the 70-kDa molecules, indicating a possible participation of specific antibodies to this molecule in infection control. In an other work of the our group, we produced a mAb against a 70-kDa glycoprotein of S. schenckii in order to better understand the effect of passive immunization of mice infected with S. schenckii. Results showed a significant reduction in the number of CFU in organs of mice when the mAb was injected before and during S. schenckii infection. Similar results were observed when T-cell deficient mice were used. Drugs of choice in the treatment of sporothrichosis require long periods and frequently relapses are observed, mainly in immunocompromized patients. The strong protection induced by mAb against a 70-kDa glycoprotein makes it a strong candidate for a therapeutic vaccine against